2003
DOI: 10.1034/j.1600-0838.2003.02477.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the understanding of the repeated bout effect: the protective effect against muscle damage from a single bout of eccentric exercise

Abstract: The repeated bout effect refers to the adaptation whereby a single bout of eccentric exercise protects against muscle damage from subsequent eccentric bouts. While the mechanism for this adaptation is poorly understood there have been significant recent advances in the understanding of this phenomenon. The purpose of this review is to provide an update on previously proposed theories and address new theories that have been advanced. The potential adaptations have been categorized as neural, mechanical and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
423
6
40

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(485 citation statements)
references
References 74 publications
(136 reference statements)
16
423
6
40
Order By: Relevance
“…1,3 When eccentric exercise is repeated, the magnitude of changes in the markers is smaller and recovery of muscle function is faster compared to the initial bout. 1,4 This protective effect is often referred to as the repeated bout effect, 1,4 and is known to last for several months for the case of maximal eccentric exercise of the elbow flexors. 5 It has been reported that a reduced number of maximal eccentric contractions can provide a protective effect against a larger number of maximal contractions.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 When eccentric exercise is repeated, the magnitude of changes in the markers is smaller and recovery of muscle function is faster compared to the initial bout. 1,4 This protective effect is often referred to as the repeated bout effect, 1,4 and is known to last for several months for the case of maximal eccentric exercise of the elbow flexors. 5 It has been reported that a reduced number of maximal eccentric contractions can provide a protective effect against a larger number of maximal contractions.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of CK concentration observed over time in this study may be ascribed to muscle adaptation 26 , which has been observed in protocols of eccentric exercise 27 and in soccer players during a Brazilian first-division championship 10 . One of the mechanisms responsible for muscle adaptation can be derived from the activation of myogenic satellite cells that act in the repair of damaged muscle fibers 28 .…”
Section: Discussionmentioning
confidence: 85%
“…CK activity after the second bout of high volume squatting was reduced by the initial lower volume bout, meaning it is unlikely that the RBE was exclusively due to the removal and replacement of weak sarcomeres as proposed by some studies (e.g. Armstrong et al 1983;Byrnes et al 1985;McHugh et al 2003;McHugh et al 1999). Indeed, if weak sarcomeres were still intact after the lower volume bout of squatting then they would have been damaged during the more strenuous high volume bout (Nosaka et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the lower CK in Bout 2 suggests that the initial stress in Bout 1, albeit of a lower intensity, provided a stimulus to strengthen the muscle cell membrane against further damage (Clarkson and Tremblay 1988;Howatson et al 2007). The protective effect of lower volume muscle-damaging exercise against subsequent high volume exercise could also be due to changes in motor unit recruitment during squatting Bout 2 (Chen 2003;Howatson et al 2007;McHugh 2003;McHugh et al 1999). Unfortunately EMG activity was measured during running and not the damaging exercise, which means that we are unable to confirm if alterations in motor unit activity occurred.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation